Excluding students with disabilities from the culture of achievement: the case of the TIMSS, PIRLS, and PISA - Schuelka, Matthew J. (Journal of education policy, 2013)
International tests of achievement narrowly measure specific academic subjects, but have larger educational policy implications. These tests come to summarize national education systems and are used in national and international discourse. However, students with disabilities are being entirely excluded from participation in the discourse of achievement. The Trends in International Mathematics and Science Study, Progress in International Reading Literacy Study, and Programme for International Student Assessment all actively exclude students with disabilities from being measured when the testing agencies set up 'desired target populations' and report out on testing participation. This exclusionary discourse establishes that students with disabilities do not belong in a culture of achievement and educational evaluation, which has an impact on policies concerning educational equity and maintains the oppression of low expectations. US policy requires that 95% of all students take achievement tests and be given reasonable accommodations. This paper concludes that international achievement tests should follow the same standard.